Clustering of malignant pleural mesothelioma in asbestos factories: a subgroup analysis in a 29-year follow-up study to identify high-risk industries in Taiwan. Issue 12 (9th December 2018) - Lee, Lukas Jyuhn-Hsiarn; Lin, Cheng-Kuan; Pan, Chih-Hong; Cheng, Yawen; Chang, Yu-Yin; Liou, Saou-Hsing; Wang, Jung-Der
Abstract : Objective: Exposure to asbestos is the major cause for malignant pleural mesothelioma (MPM), but the causal link of individual cases is difficult to establish for lack of exposure information and long disease latency. Methods: We established a retrospective cohort of workers employed in asbestos industries during the period of 1950–1989 and the occurrence of MPM during the period of 1980–2009 was examined with the Taiwan Cancer Registry. Estimated rate ratios (eRRs) were computed for each factory where any case of MPM was diagnosed by assuming Poisson distribution with a minimal latency of 20 years. Results: A total of 18 MPM (17 males, 1 female) in eight factories were found. The incidence rate of MPM for the eight factories was 18.0 per million, ranging from 6.2 per million (military factory) to 268.2 per million (asbestos cement). We observed significantly increased risks for MPM in asbestos cement, thermal insulation and shipbuilding industries, with eRR (genders combined) of 113.6, 87.5 and 15.8, respectively. The sensitivity analyses considering latency showed similar findings in latency ≥ 30 years, and the shipbuilding industry presented a significant eRR given a latency ≥ 40 years. The gender-specific eRR showed similar results in men, but high eRR of 729.6 was observed in an asbestos cement factory where a female MPM was diagnosed. Conclusions: This nationwide study in Taiwan comprehensively shows that different asbestos manufacturing processes, including asbestos cement, thermal insulation and shipbuilding industries, were at significantly increased risks for MPM. We recommend to establish a medical screening programme for workers previously exposed to asbestos to identify MPM and other asbestos-related diseases at an earlier stage.